Knowledge, attitude and practice on hand hygiene among clinical year medical students in Islamic institution - Abd. Aziz, Karimah Hanim; Mohd Rus, Razman; Ab Rahman, Jamalludin; Nasreen, Hashima E; Pasi, Hafizah (2016)
Background: Hand hygiene has been recognized as the leading measure in preventing healthcare-associated infections (HCAIs) and transmission of pathogenic microorganisms in hospital setting. Previous researches showed low compliance of healthcare workers towards this measure. Thus, there is a need to assess the hand hygiene knowledge (K), attitude (A) and practice (P) among medical students as they also pose threat in transmitting nosocomial infections to patients during their training period. Objectives: This study aimed to measure the level of knowledge, attitude and practice of clinical year medical students in IIUM Kuantan towards hand hygiene and its associated factors. Methods: A cross-sectional study was conducted among 231 clinical year medical students in IIUM Kuantan from 27th June 2016 until 29th July 2016 using selfadministered questionnaire. Universal sampling was applied. Knowledge was evaluated using World Health Organization (WHO) questionnaire; while attitude and practice was assessed using validated questionnaire adapted from Centers for Disease Control and Prevention (CDC) Hand Hygiene Guidelines. Descriptive statistics and univariate test were used whenever appropriate for analysis using IBM SPSS Statistics for Windows version 23.0. Results: Majority of the students (99.6%) had good knowledge on hand hygiene. However, only 59.3% showed good attitude towards hand hygiene while 55.0% of them exhibited good hand hygiene practices. Univariate analysis found that those who have formal training and had been in surgical posting showed good attitude (p = 0.004 and p = 0.017 respectively) and who had been in surgical posting and had good attitude exhibited good practice (p <0.001 and p= 0.019 respectively). Conclusion: The relatively low score of attitude and practice compared to knowledge on hand hygiene demand a special attention. Hand hygiene training sessions need to be done in continuous monitoring to encourage medical students to follow correct practices and inculcate good attitude.